Regulation of Plea Bargaining Policy as a Novelty in Criminal Justice System to Create Effective and Efficient Criminal Law Enforcement: A Study of Ruu Kuhap - Seraphinus Mariano Agung Serman; Umi Rozah (Dinasti Research, 2025)
The criminal justice system in Indonesia faces various challenges, such as lengthy judicial processes and case backlogs in the courts. To address these issues, reforms in the criminal justice system are necessary, one of which is the implementation of